Towards a new history of work - International Conference on Labour History 2012 : V. V. Giri National Labour Institute); Bhattacharya, Sabyasachi, 1938-; Association of Indian Labour Historians; V.V. Giri National Labour Institute (New Delhi : Tulika Books in association with Association of India n Labour Historians and V.V. Giri National Labour Institute, 2014)
Papers presented at the 9th International Conference on Labour Histo ry, held at V.V. Giri National Labour Institute during 22-24 March 2012 .
Includes bibliographical references.